Evaluation of Prescription Pattern of Antibiotic Prophylaxis in Patients Undergoing Orthopedic Surgical Procedures and Their Clinical Outcomes in Jahrom - Mirzaei , Maryam; Pourmokhtari , Masoumeh; Sepahvand, Elham (Journal of Clinical Physiotherapy Research, 2019)
Introduction: Surgical site infection (SSI), after orthopedic surgery and arthroplasty, is associated with serious outcomes, including significant increases in length of stay, re-admissions, health costs, and mortality rates, many of which can be prevented. The aim of the present study was to investigate the clinical outcomes of prescription pattern of antibiotic prophylaxis in adult patients undergoing orthopedic surgical procedures at Peymanieh Hospital in Jahrom, Iran. Materials and Methods: The present cross-sectional study was carried out on 280 patients referred to the Orthopedic Department of Peymaniyeh Hospital of Jahrom in 2016. Data collection was carried out using a researcher-made checklist, which included three parts: demographic information, prescription characteristics of prophylactic antibiotics, recording side effects, and clinical outcomes. Data analysis was carried out using Chi-square or Fisher's exact test for qualitative variables and independent-samples t-testi n SPSS ver. 19. Results: A total of 280 subjects with a mean age of 38.4 ± 20.3 years were investigated. The mortality rate was zero percent, and no pulmonary and renal complications, wound dehiscence, and secondary nosocomial infections were observed. The only complication observed and recorded among individuals was superficial wound infection, which was observed in 8.3% of patients (n=25 patients). There was a significant relationship between superficial wound infection with sex, type of surgery, and site of injury (P<0.05). Conclusion: The antibiotic prophylaxis protocol used prior to orthopedic surgery in Jahrom was based on standard patterns, but there was a significant wound infection and it is recommended to carry out further studies in this regard. Keywords: Orthopedic surgery, Wound infection, Hospitalization, Nosocomial infection, antibiotic prophylaxis